2016
DOI: 10.1021/acs.chemrev.6b00166
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic–Peptide Bioconjugates: Synthetic Strategies and Medicinal Applications

Abstract: Peptides are important biological molecular entities in biomedical research. They can be prepared in a large variety of shapes, with a host of chemical functions, and tailored for specific applications. Organometallic medicinal chemistry is a relatively young field that explores biomedical and bioanalytical applications of organometallic complexes, that is, metal compounds with at least one direct, covalent metal-carbon bond. The conjugation of peptides to such medicinally active organometallic moieties starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(97 citation statements)
references
References 313 publications
2
93
0
2
Order By: Relevance
“…The cytotoxicity of complex 4 (IC50=26±2 μ m after 24 h, 38±2 μ m after 48 h and 41±2 μ m after 72 h) is higher than for the positive control cisplatin. This result is consistent with previously disclosed studies for water‐soluble gold(I) phosphane complexes, which reported IC50 values between 1 μ m and 100 μ m , depending on the cell line, incubation time, ligand type and lipophilicity of the gold(I) complexes …”
Section: Resultssupporting
confidence: 93%
“…The cytotoxicity of complex 4 (IC50=26±2 μ m after 24 h, 38±2 μ m after 48 h and 41±2 μ m after 72 h) is higher than for the positive control cisplatin. This result is consistent with previously disclosed studies for water‐soluble gold(I) phosphane complexes, which reported IC50 values between 1 μ m and 100 μ m , depending on the cell line, incubation time, ligand type and lipophilicity of the gold(I) complexes …”
Section: Resultssupporting
confidence: 93%
“…Mechanistische Vorschläge für diesen Prozess gibt es bereits,d och fehlt es zumeist an konkreten Belegen. [142][143][144][145][146][147] Weitere komplementäre Metallierungsansätze basieren auf der Inkorporierung [143,[148][149][150][151][152] einer nichtnatürlichen Aminosäure mit metallbindender Seitenkette (z. Obwohl sie auf eine einzige Gruppe an Funktionalisierungen beschränkt ist, hat sich die Azidgruppe zu einem essenziellen Bestandteil der gängigen Biokonjugationsmethoden entwickelt und die oben beschriebene Te chnik wurde bereits von verschiedenen Arbeitsgruppen ausführlich angewendet.…”
Section: Angewandte Chemieunclassified
“…As a new approach to rationalize the metal‐based drug design, ferrocene has been incorporated into the principal structural component of natural and synthetic compounds with biological activity to develop more selective and effective metal‐based drugs . This approach has been applied in hormone‐dependent breast cancer, in which ferrocene has been vectorized with estrogen hormones in order to effectively deliver its moiety to cancer tissues .…”
Section: Introductionmentioning
confidence: 99%